Road infrastructure distance indicators and relationship with affordability of housing/ Mohamad @ Masri ... [et al.] - Mohamad @ Masri, Muhamad Hilmi; Sa'ad, Mohd Farid; Azman, Najma; Aliasak, Mohd Hasrol Haffiz; Mohd Lazi, Mohd Khairul Afzan; Md Wadzir, Mohamad Fitry (Universiti Teknologi MARA, Perak, 2023)
This paper looks at the road infrastructure distance indicators and explores the relationship with the affordability of housing. This paper focuses on the aspect of the built environment in Malaysia, with some review of ASEAN and Asian regions. The paper aims to outline the road infrastructure indicators based on distance and find out its relationship with housing affordability. The objective of this paper is to provide road infrastructure indicators based on distance and affordability of housing. The methodology of this review paper is the implementation of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and two main journal databases: Web of Science and Scopus. Based on the SLR conducted, the researchers have extracted seven main themes: traffic number, commute cost, vehicle mobility, travel time, workplace distance, road network distance and house desirability. The findings were then utilised in determining affordable housing relationships with the indicators and within the Malaysian context. The themes were then expected to become the basis for future data collection processes by the researchers.